ShapeWordle: Tailoring Wordles using Shape-aware Archimedean Spirals - Wang, Yunhai; Chu, Xiaowei; Zhang, Kaiyi; Bao, Chen; Li, Xiaotong; Zhang, Jian; Fu, Chi-Wing; Hurter, Christophe; Deussen, Oliver; Lee, Bongshin (IEEE Transactions on Visualization and Computer Graphics, 2020)
We present a new technique to enable the creation of shape-bounded Wordles, we call ShapeWordle, in which we fit words to form a given shape. To guide word placement within a shape, we extend the traditional Archimedean spirals to be shape-aware by formulating the spirals in a differential form using the distance field of the shape. To handle non-convex shapes, we introduce a multi-centric Wordle layout method that segments the shape into parts for our shape-aware spirals to adaptively fill the space and generate word placements. In addition, we offer a set of editing interactions to facilitate the creation of semantically-meaningful Wordles. Lastly, we present three evaluations: a comprehensive comparison of our results against the state-of-the-art technique (WordArt), case studies with 14 users, and a gallery to showcase the coverage of our technique.